A Case Study of Inventory Analysis in a Healthcare Product Manufacturing Company - Mohd Kamarul Irwan Abdul Rahim; Quamrul Hassan; Santhirasegaran S.R. Nadarajah; Kamaruddin Radzuan (International Journal of Supply Chain Management, 2018)
A worldwide market inventory is one of the biggest and most significant resources of a manufacturing industry. ABC analysis is one of the techniques used comprehensively in manufacturing industries for inventory classification. The ABC inventory classification technique has an efficient control on a huge amount of inventory items. The ABC inventory classification approach categorizes inventory items as A, B and C classes according to their annual consumption value. To direct and control the inventory items more proficiently the inventory managers regularly classify and group all the inventory items. Thus, in this paper, we concentrate on inventory management in a healthcare product manufacturing company in Kedah, Malaysia. A case study approach is used to make a preliminary inventory assessment through ABC analysis in order to control the inventory items more efficiently.